Efficacy and safety of autologous adipose tissue-derived stromal vascular fraction in patients with thin endometrium: a protocol for a single-centre, longitudinal, prospective self-control study - Rong Li; Yang Yu; Shuo Yang; Fen-Ting Liu; Tian-Liu Peng (BMJ Open)
Introduction Endometrial thickness is an important parameter to evaluate endometrial receptivity. An appropriate endometrial thickness is necessary for both embryo implantation and maintaining normal pregnancy. Women with thin endometrium are one of the critical challenges in the clinic, and current therapeutic strategies for thin endometrium remain suboptimal. The stromal vascular fraction (SVF) derived from adipose tissue contains a variety of cells, mainly adipose-derived stem/stromal cells and adipose cells. Recently, adipose tissue-derived SVF showed tremendous potential for treating thin endometrium due to its capacity to repair and regenerate tissues. The application of SVF in animal models for treating thin endometrium has been investigated. However, limited evidence has demonstrated the efficacy and safety of autologous SVF in patients with thin endometrium.Methods and analysis This study is a single-centre, longitudinal, prospective self-control study to investigate the preliminary efficacy and safety of autologous SVF in improving the pregnancy outcome of infertile patients with thin endometrium. Thirty patients diagnosed with thin endometrium will be recruited based on the inclusion and exclusion criteria. The SVF suspension will be transferred into the uterine cavity via an embryo transfer catheter. Then, comparisons between pretreatment and post-treatment will be analysed, and the outcomes, including endometrial thickness, menstrual volume and duration, frequency and severity of adverse events and early pregnancy outcomes, will be measured within a 3-month follow-up, while late pregnancy outcomes and their offspring will be followed up via telephone for 2 years. The proportion of patients with improved symptoms will be calculated and compared.Ethics and dissemination This study was approved by the Ethics Committee of Peking University Third Hospital (reference number: REC2020-165). Written informed consent will be provided for patients before being included. The results will be presented at academic conferences and a peer-reviewed journal.Trial registration number ChiCTR2000035126.